Effect of Advanced Shoe Technology on the Evolution of Road Race Times in Male and Female Elite Runners - Bermon, Stéphane; Garrandes, Frédéric; Szabo, Andras; Berkovics, Imre; Adami, Paolo Emilio (Frontiers in Sports and Active Living, 2021)
Influence of advanced footwear technology (thickness of light midsole foam and rigid plate) on distance running performances was analysed during an eight-year period. Analysis of variance was used to measure effects of time, gender, shoe technology, and East-African origin on male and female top 20 or top 100 seasonal best times in 10 kilometres, half marathon, and marathon. In both genders and three distance running events, seasonal best times significantly decreased from 2017, which coincides with the introduction of the advanced footwear technology in distance running. This performance improvement was of similar magnitude in both East-African and non-East-African elite runners. In female elite athletes, the magnitudes (from 1.7% to 2.3%) of the seasonal best time decrease between 2016 and 2019, were significantly higher than in their male counterparts (from 0.6% to 1.5%). Analyses of variance confirmed that the adoption of the advanced footwear technology significantly improved top 20 seasonal best times in female half marathon and marathon, and male marathon; improvements being more pronounced in female and in long distance running events. The adoption of this new shoe technology improved female marathon time by approximately 2 minutes and 10 seconds which represents a significant 1.7% increase in performance.